Interpretation of isotopic ages and 87 Sr/ 86 Sr initial ratios for plutonic rocks in the Whitehorse map area, Yukon - Morrison, Gregg W.; Godwin, Colin I.; Armstrong, Richard L. (Canadian Journal of Earth Sciences, 1979)
Sixteen new K–Ar dates and four new Rb–Sr isochrons help define four plutonic suites in the Whitehorse map area, Yukon. The Triassic(?) suite, defined on stratigraphic evidence, is the southern extension of the Yukon Crystalline Terrane and is correlative with plutonic suites in the Intermontane Belt in British Columbia. The mid-Cretaceous (~100 Ma) suite in the Intermontane Belt in the Whitehorse map area is time equivalent to plutonic suites in the Omineca Crystalline Belt to the east. Late Cretaceous (~70 Ma) and Eocene (~55 Ma) suites include volcanic and subvolcanic as well as plutonic phases and are correlative with continental volcano–plutonic suites near the eastern margin of the Coast Plutonic Complex. The predominance of the mid-Cretaceous suite in the Intermontane Belt in Whitehorse and adjacent map areas in Yukon and northern British Columbia suggests that this area has undergone posttectonic magmatism more characteristic of the Omineca Crystalline Belt than of the Intermontane Belt elsewhere in the Canadian Cordillera. 87 Sr/ 86 Sr initial ratio determinations suggest that the southern extension of the Yukon Crystalline Terrane in the western part of the Whitehorse map area and in northern British Columbia includes Precambrian crust separated from the North American craton by Paleozoic oceanic crust of the Intermontane Belt.